Wpływ polszczyzny na przemiany językowe religijnych tekstów cyrylickich katechizmów unickich w Rzeczypospolitej XVIII wieku (na przykładzie Katechizmu supraskiego z 1722 roku i Katechizmu poczajowskiego z 1768 roku) - Skivitski, Dzmitry (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article discusses the influence of Polish on the evolution of Ruthenian Uniate Church’s liturgical language in the eighteenth century in the Polish-Lithuanian Commonwealth according a catechism text published in the Supraśl and Pochayiv Basilian Order Monasteries in 1722 and 1768. The Ruthenian Uniate Church catechism constitutes the basis for the linguistic analysis. The main objective of the article is to investigate how Middle Polish influenced the developing liturgical language of the Ruthenian Uniate Church. After analysing the text’s language, it could be said that in the period from the foundation of that church to the three partitions of the Polish-Lithuanian Commonwealth, Polish language had significant influence on the evolution of the church’s liturgical language and affected its phonetics and morphology.